Mucosal Autoimmunity to Cell-Bound GP2 Isoforms Is a Sensitive Marker in PSC and Associated With the Clinical Phenotype - Sowa, Mandy; Kolenda, Rafał; Baumgart, Daniel C.; Pratschke, Johann; Papp, Maria; Tornai, Tamas; Suchanski, Jaroslaw; Bogdanos, Dimitrios P.; Mytilinaiou, Maria G.; Hammermann, Jutta; Laass, Martin W.; Conrad, Karsten; et al. (Frontiers in Immunology, 2018)
Introduction: Zymogen granule glycoprotein 2 (GP2) was demonstrated as first autoimmune mucosal target in primary sclerosing cholangitis (PSC) associated with disease severity. Autoantibodies to four GP2 isoforms (aGP21-4) were found in patients with inflammatory bowel diseases but reactivity against specific GP2 epitopes has not been investigated in PSC yet. Hence, the prevalence of aGP21-4 and their association with the PSC phenotype for risk prediction were examined. Methods: GP2 isoforms were stably expressed as glycosylphosphatidylinositol-anchored molecules in the membrane of HEp-2-cells and used as autoantigenic targets in indirect immunofluorescence assay (IFA). aGP21-4 IgA and IgG were detected by IFA in 212 PSC patients of four European university hospitals and 145 controls comprising 95 patients with cystic fibrosis and 50 healthy subjects. Results: Combined aGP21 and aGP24 IgA testing with a sensitivity of 66.0% and a specificity of 97.9% resulted in the best diagnostic performance (Youden index: 0.64) regarding all aGP2 and combinations thereof. aGP24 IgA positivity is significantly associated with the presence of cirrhosis in PSC (p=0.0056). Logistic regression revealed the occurrence of aGP21 IgA (odds ratio [OR] 1.38, 95% confidence interval [CI]: 1.03-1.86) and aGP24 IgA (OR 1.52, 95%CI: 1.07-2.15) along with male gender (OR 0.51, 95%CI: 0.27-0.97) and older age (OR 1.03 95%CI: 1.01-1.05) as significant risks for the concomitant presence of cirrhosis in PSC. Conclusions: Combined aGP21 and aGP24 IgA analysis is preferred to single aGP2 isoform analysis for sensitive PSC autoantibody testing. Positivity for aGP21 and aGP24 IgA is associated with cirrhosis in PSC and could be used for risk stratification.